Office 365: Migrating and Managing Your Business in the Cloud - Don Crawford (Apress, 2013)
Written for the IT professional and business owner, this book provides the business and technical insight necessary to migrate your business to the cloud using Microsoft Office 365. This is a practical look at cloud migration and the use of different technologies to support that migration. Numerous examples of cloud migration with technical migration details are included. Cloud technology is a tremendous opportunity for an organization to reduce IT costs, and to improve productivity with increased access, simpler administration and improved services. Those businesses that embrace the advantages of the cloud will receive huge rewards in productivity and lower total cost of ownership over those businesses that choose to ignore it. The challenge for those charged with implementing Microsoft Office 365 is to leverage these advantages with the minimal disruption of their organization. This book provides practical help in moving your business to the Cloud and covers the planning, migration and the follow on management of the Office 365 Cloud services.